Effects of knee alignment on human gait based on wireless sensors. (1st January 2013) - Saga, Norihiko; Irie, Saeko; Nakanishi, Yasutaka; Dobashi, Hiroki; Sogabe, Akitoshi
This study has been conducted to measure human gait locomotion according to different lower extremity alignments, and to assess the alignment effects on knees and leg muscles. Subjects were separated into three groups by knee alignment as normal knee, genu varum, and genu valgum. We conducted a synchronisation experiment using motion capture, tactile sensor and muscle potential in order to investigate the effect of the muscle activity due to differences in the alignment of the knee, and we are considering the difference in the motion analysis during walking, ground reaction and EMG. The results, were differences in the EMG and walking motion by knee types.